Analysis of Drug Related Problems (DRPs) in Patient with Chronic Kidney Disease Stage V, Anemia and Cholelithiasis With Hemodialysis Therapy - Kurniawan, Hery (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The use of medical therapy in patient with chronic kidney disease stage v, anemia and cholelithiasis needs special attention. The case report aims to discuss the treatment therapy for chronic kidney disease stage v, anemia and cholelithiasis that the patient is currently suffering from. Data collection method is retrospective. The data obtained was then analyzed for Drug Related Problems using a literature review. Based on the results of this analysis, the treatment given to the patient was deemed appropriate. The results of the analysis show that it is necessary to periodically monitor gallstone size, kidney function (serum creatinine and urea) and hemoglobin.